Rhythmic rhyme in the poetry of Dr. Miqdad Rahim (Journal of the College of Basic Education, 2024)
The research aims to identify the second pillar of poetic music after meter, which is rhyme, taking the poetry of the poet Dr. Miqdad Rahim in its vertical and free styles as an applied space, as we dealt with the rhyme of vertical poetry, whether it is unified, which is the majority, or diverse, which is the few, and the rhyme of ta’feela poetry. And the themes it adds to the rhyme, and the difference or diversity that the two styles create in the rhyme of Arabic poetry, and whether the poet excelled in them, and in which of them he excelled, strengthening our analysis with statistical tables.